The Effectiveness of Webinars in Promoting Researchers’ Research Output in Higher Education Case of EFL Researchers at the University of Batna 2 - عقون, وفاء (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
This study is a reflection on the inclusion of webinars in higher education as an innovative tool to develop EFL researchers’ research profile. The study assumes that there is a positive correlation between researchers’ satisfaction in webinars and their personal attributes. After the statistical processing of the data collected, findings suggest that webinars have great potential for increasing researchers’ research performance and research productivity. Moreover, the study verifies that researchers’ personal attributes, particularly age, gender and academic rank are statistically related to the preference of factors in the favor of webinars in higher education. The implications of the study's findings can inform events’ organizers, researchers, teachers and students interested in doing webinars.